2018
DOI: 10.1186/s40662-018-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power calculation in eyes with previous corneal refractive surgery

Abstract: BackgroundThis review aims to explain the reasons why intraocular lens (IOL) power calculation is challenging in eyes with previous corneal refractive surgery and what solutions are currently available to obtain more accurate results.ReviewAfter IOL implantation in eyes with previous LASIK, PRK or RK, a refractive surprise can occur because i) the altered ratio between the anterior and posterior corneal surface makes the keratometric index invalid; ii) the corneal curvature radius is measured out of the optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 79 publications
1
103
0
8
Order By: Relevance
“…However, the clinical historical data from the time of the refractive surgery are often missing or incomplete. Many studies indicated that the accuracy of IOL power prediction of the clinical history method was significantly lower than other methods [4]. Thus, we did not analysis the methods using clinical historical data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical historical data from the time of the refractive surgery are often missing or incomplete. Many studies indicated that the accuracy of IOL power prediction of the clinical history method was significantly lower than other methods [4]. Thus, we did not analysis the methods using clinical historical data.…”
Section: Discussionmentioning
confidence: 99%
“…For most myopic patients, the need for spectacles and hyperopia shift after cataract surgery were particularly disturbing. Three main sources of error in IOL calculation after corneal refractive surgery exist: radius measurement error [2], keratometer index error [3] and IOL formula error [4].…”
Section: Introductionmentioning
confidence: 99%
“…Over 2 million patients have undergone SMILE, including 1 million Chinese patients. An unfortunate consequence of corneal refractive surgery is difficulty in accurately calculating intraocular lens (IOL) power in eyes undergoing cataract surgery [5]. During the last few decades, IOL power calculation after keratorefractive surgery has been the subject of numerous studies and publications [6].…”
Section: Introductionmentioning
confidence: 99%
“…2 Fourth, several reports in the literature described formulas to calculate IOL power mainly after photorefractive keratectomy and LASIK, but only few after radial keratotomy. 4 The authors checked some of them, but not evaluated others such as the contact lens method described by Soper et al 4 and the method based on a regression formula applied to R Factor method, proposed by Rosa et al 5 We understand why the authors could not compare the method by Soper et al, but the formula described by Rosa et al did not require the knowledge of patient's history, neither special examination, and this method has demonstrated to improve refractive outcomes and we wonder why it was not evaluated among the other no-history methods. We appreciate De Bernardo and coworkers' interest in this topic and their comments on our article.…”
mentioning
confidence: 99%
“…The R Factor method was initially described by Rosa et al 2 in 2005 for use after LASIK and photorefractive keratectomy, but so far has not gained traction in terms of being included in either the American Society of Cataract and Refractive Surgery calculator or other recent reviews of this topic. 3,4 In a 2011 study of 9 intraocular lens calculation formulae for postmyopic LASIK eyes, several of which have since been superseded by improved methods, the R Factor was found to be one of the least accurate. 5 We admit to not being aware of the R Factor being used in the context of postradial keratotomy eyes, which differ considerably from post-LASIK and photorefractive keratectomy eyes, and indeed a Pubmed search of ["radial keratotomy" AND "R factor"] performed on April 29, 2020 returned zero results.…”
mentioning
confidence: 99%